Retail Electricity Tariffs for Electric Vehicles in Europe: A Multivariate Analysis in 4 European Countries. Issue 9 (2022) - Bairrão, D.R.; Soares, J.; Canizes, B.; Lezama, F.; Vale, Z.
Abstract: During the past few years the transport matrix received many policies to push for the sector decarbonization. The electric vehicles and charging infrastructure increased a lot motivated by European Union directives and countries legislations, becoming national policies framework. Considering the electricity market dynamics, the electrification of transport created a new challenge going forward. In this context, this paper presents a multivariate analysis of electricity commercialization and charging infrastructure to evaluate the real state of electricity mobility and design future opportunities. The analysis uses tariffs, commercialization models, charging services and economic indicators of four countries. A comprehensive simulation model estimates the total electric mobility bill per country and the portion of the average salary spent with the car charging. Even considering the best scenario, consumers from Portugal commit almost four percent of its average wage while Norway commit only one percent. The results reveal that long-term commitment with energy planning, generation and energy matrix expansion, implies on lower energy costs; better economic actions also imply on lower energy expenditure for costumer. The hourly tariffs are important alternatives to reduce energy costs and manage demand helping network operators to plan and manage the energy system.